EFFICACY OF ENTOMOPATHOGENIC FUNGI Beauveria (NFCCI -ACCESSION NUMBER: 4225). (HYPOCREALES: CORDYCIPITACEAE) AND Metarhizium anisoplae (METCHNIKOFF)) (HYPOCREALES: CLAVICIPITACEAE) AGAINST GREY WEEVIL Myllocerus Sp. (COLEOPTERA: CURCULIONIDAE) IN KASARAGOD DISTRICT OF KERALA, INDIA - RAJAN, N. RANJINI; GHOSH, S. M. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2020)
Grey weevil, Myllocerus Schoenherr (Coleoptera: Curculionidae) has been a nuisance to the farmers over decades. The study revealed the efficacy of two potential entomopathogenic fungi, one the field collected Beauveria (Hypocreales: Cordycipitaceae) with NFCCI accession No. 4225 and the other Metarhizium anisoplae (Metchnikoff) (Hypocreales: Cordycipitaceae) against the adults and fourth instar larvae of Myllocerus sp. The result showed high adult mortality (100%) at 4.56x108 Conidia/ml of field collected Beauveria after 240 hours of treatment. M. anisoplae treatment has resulted 90% adult mortality at 5.36x108 after 240 hours of treatment. The larval mortality was very small when compared to adult mortality. The median lethal time for the most effective dose of Beauveria (4.56x108) was 70.48 hours and for the most effective dose of M. anisopliae (5.36x108 conidia/ml) was 99.14 hours. In the present study Beauveria sp. showed a more lethal effect against grey weevils.